Early Complications in Acute versus Elective Cases of Laparoscopic Cholecystectomy in Tertiary Hospitals: A Comparative Study - Raza Haider; Muhammad Qasim Butt; Jamil Salamat Ullah; Mansoor Tariq Azim; Afnan Akbar (Pakistan Armed Forces Medical Journal, 2023)
Objective: To correlate the operative findings of patients undergoing laparoscopic cholecystectomy, either acute or elective, with surgical complications and conversion to open cholecystectomy.